Traditional knowleadge of basketry practices in a northeastern region of Portugal - Carvalho, Ana Maria (2008)
The aim of this paper is to study the plants species and techniques used for basket making and its social context, in rural communities of the Natural Park of Montesinho, in north-eastern Portugal